“It’s not Easy to Speak English”: International Students’ Language Anxiety in Academic Intercultural Communication Practices - Dewi Zakiya, Evi; Kusumaningputri, Reni; Khazanah, Dewianti (JEELS (Journal of English Education and Linguistics Studies), 2022)
During the past few years, an increasing number of international students from Thailand have come to Indonesian campuses to pursue their undergraduate degree in the departments they selected, including in the department of English. What is it like to learn to speak English as international students in the context of English as a foreign language? As they come from a country where English is taught and learnt as a foreign language, what challenges they face in relation to speaking? The study reported the anxiety experiences of five international students from Thailand as they engaged in English use and learning situations in Indonesia. Drawing on a narrative inquiry method, the results revealed that self-esteem, social environment, fear of making mistakes, the formal classroom environment, social status and self-identity, cultural differences, presentation in the classroom, and the university admission system were reasons for their language anxiety. The study also offers insights into how international students who learn English in Indonesia can be better supported during their stay in Indonesia as a host country.